Збереження Gentiana lutea L. в природі з використанням культури ex situ - Москалюк, Б.І. (Промышленная ботаника, 2013)
Приведены результаты шестилетнего культивирования G. lutea. Показаны изменения вегетативных органов растения на ранних этапах онтоморфогенеза. На основании оригинальных исследований определены особенности культивирования G. lutea. Показано перспективу сохранения вида ex situ. This paper reviews the results of cultivating of G. lutea for six years. The study has shown that there are certain changes in vegetative organs of plants in the early stages of ontomorphogenesis. Based on the original research, the features of G. lutea cultivation are determined. The principal attention is paid to the need of G. lutea ex situ preservation.